Experience of awake craniotomy in a child (clinical case) - O. N. Pulkina; D. V. Nizolin; Zh. Zh. Sholahov; A. A. Zhaigalov; A. V. Kim; G. N. Kasenova; O. O. Shmeleva (Вестник анестезиологии и реаниматологии)
The objective was to demonstrate the possibility of performing awake craniotomy in a child.Materials and methods. The 9-year-old child with a dysembrioplastic neuroepithelial tumor in the left temporal lobe was planned and performed awake craniotomy. During awakening, the child performed a naming test, object designation tests, word repetition and spontaneous speech, and Luria’s test.Results. During psychological tests and intraoperative neuromonitoring, it was possible to successfully identify the speech zone and motor areas of the face, which helped to safely remove brain formation without complications. This clinical case was also interesting because the child’s native language was Kazakh, so an interpreter was presented during the intraoperative awakening.Conclusions. The case demonstrates the possibility of performing awake craniotomy in a child, which depends not only on the somatic and psychological state, but also on the professionalism of the operating team, including surgeons, anesthesiologists, neurophysiologist, neuropsychologist and a large number of nursing staff who are able to clearly interact with each other.